The tutor-learner relationship in literacy education: Redefinition or reproduction? - Linda Ziegahn; Kathleen H. Hinchman (Adult Education Research Conference, 1993)
A qualitative study of university students working in literacy classrooms suggested that tutors felt most successful when they helped low-literate adults to develop academically and personally. There was minimal evidence of tutors playing the role of critical educators in questioning social inequities.